The effect of employees' attributes towards customer satisfaction - Abu Hassan, Muhamad Syafiq; Agus Salim, Muhamad Syamsul Hadi; Abdullah, Rahman; Rahman, Razman; Zahari, Harnizam (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The fast-food industry's customer service has undergone substantial improvements to align with evolving consumer expectations and continuous innovations in service delivery. The objective of this study is to investigate the relationship between employee traits and the level of customer satisfaction in fast food chains in Dungun, Terengganu. The study highlighted the importance of customer experience and the contribution of these employee attributes including empathy, reliability, responsiveness, cultural sensitivity, hygiene compliance, and professionalism to customer experience and satisfaction. This research demonstrates the value of positive employee interactions in developing customer trust, improving service quality, and creating loyalty.